Singing Birds, English Romanticism, and Two Bengali Bards in Their Late Romantic Phase - Alam, Fakrul (Spectrum, 2022)
The paper examines how English romanticism in general and romantic poets, in particular, had an impact on concepts of romanticism in our part of the world and why it is important to understand their influence. It argues that we must look at interactions between our leading Bengali poets and their English counterparts to determine the imaginative lineage of the Bengali poets. It specifically focuses on the relationship between birds and bards, and romantic poetic imaginings of the avian lot in Rabindranath and Jibanananda in their late-romantic phase. Spectrum, Volume 16, June 2021: 115-126